Meningkatkan Hasil Belajar IPS Menggunakan Media Pop-Up Pada Siswa Kelas V SD Negeri 29 Kota Ternate - Tauhid, Rachmatia (Peneliti.net, 2023)
This research aims to determine the improvement in Social Sciences (IPS) learning outcomes for fifth grade students at SD Negeri 29 Ternate City by using pop-up media. This type of research is Classroom Action Research (PTK). The subjects of this research were class V students at SD Negeri 29 Ternate City with a total of 21 students. The research model used is the Kemmis and Mc model. Taggart, which consists of the planning stage, action and observation stage, and reflection stage. Data collection techniques using tests. The data analysis techniques used are quantitative analysis and qualitative analysis. To ensure the validity of the data, source triangulation techniques were used. In social studies learning activities using pop-up media, the teacher divides students into three groups, where each group gets a different pop-up book. Each student gets a student worksheet that corresponds to the material in the pop-up media. Then, group representatives present the results of their group discussions in front of the class. Using pop-up media can improve students' social studies learning outcomes. This is proven by the increase in student learning outcomes in social studies subjects, namely in the initial pre-action condition the class average learning outcomes were 64.28 with a completion percentage of 42.86%. After carrying out the actions in cycle I, the class average learning result was 73.46 with a completion percentage of 71% and after carrying out the actions in cycle II, the class average learning result was 80.47 with a passing percentage of 80.95%. This means that the research target is to increase student learning completeness in accordance with the research success indicators, namely 75% of students who take part in social studies learning using pop-up media get a score ≥ 70.